Microvascular anastomosis in a challenging setting using a 4 K three-dimensional exoscope compared with a conventional microscope: An in vivo animal study - Zhang, Zhiping; Feng, Yao; Lu, Xia; Yang, Bin; Zhang, Hongqi; Ma, Yan (Frontiers in Surgery, 2022)
BACKGROUND: Three-dimensional (3D) exoscope systems have been developed and are reported to be adequate alternatives to the conventional microscope. This study aimed to evaluate the feasibility and effectivity of microvascular anastomosis using a 4 K 3D exoscope in an in vivo animal study. METHODS: The abdominal aortas of mice were selected as the target vessels for comparing the outcomes of microvascular anastomosis for both the conventional microscope and 3D exoscope. We recorded the vessel separation, temporary occlusion, and total procedure durations. Local conditions at the sutures were also recorded. Typical histopathological images were presented, and the patency of anastomotic vessels within 5 and 30 minutes were evaluated. All procedures included both superficial and deep anastomosis. RESULTS: Sixty mice were included in the analysis; the weight and vascular diameter were 38.5±5.8 g and 0.77±0.06 mm, respectively, and around 8 stiches were required. Regarding feasibility, vessel separation duration, temporary occlusion duration, total procedure duration, blood leak, and number of vascular folds between stiches, the results were comparable between the two types of microscopes. The feasibility of anastomosis was also confirmed by pathology. Regarding effectiveness, anastomotic vascular patency at 5 and 30 minutes were similar for both microscopes. Even in the more difficult scenario of deep anastomosis, the results were comparable. CONCLUSIONS: In a highly challenging experimental setting, comparable outcomes of microvascular anastomosis were observed for the conventional microscope and 3D exoscope in these animal experiments. Therefore, in vivo microvascular anastomosis is feasible and effective using a 3D exoscope.